THE RELATIONSHIP BETWEEN JOB SATISFACTION AND EMPLOYEE SELF SERVICE APPLICATIONS ON PERSONNEL INFORMATION SYSTEM IN RETAIL STORES (CASE STUDY AT ALFAMART KLEWER BOYOLALI) - Sukmawati, Rita; Suyatno, Agus; Akhmad, Khabib Alia (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to determine the relationship between the personnel information system and employee self – service applications at the Alfamart Klewer retail store in Boyolali Regency. This study uses a quantitative method approach, which is a research problem formulation that asks about the relationship between two or more variables. The sample of this study was 70 respondents from Alfamart Klewer employees in Boyolali Regency. The method used in determining the sample was Non Probability Sampling with a purpose sampling technique. The data collection technique in this study is a questionnaire. The data analysis techniques in this study used validity tests, reliability tests, multiple linear regression tests, classical assumption tests, t-tests and f-tests (simultaneous), and coefficient of determination (R2) test using SPSS V 25. The results showed that all independent variables (relationship between, employee self – service applications and employee information) had a positive and significant relationship with the dependent variable (job satisfaction). Collectively, the independent variables, namely the personnel information system and employee self service application, provide an overall relationship with the dependent variable, namely job satisfaction.